PENGARUH LIMBAH PADAT (SLUDGE) DAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG UNGU (Solanum melongena L.) - Irna syofia; Suryawaty ,; Wanda , (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This study aimed to determine the effect of solid waste (sludge) and liquid organic fertilizer on the growth and yield of eggplant (Solanum melongena L.). The design used was          a factorial randomized block design (RAK-F) with 2 factors were investigated, namely: Factors solid waste (sludge) (S) consists of 3 levels ie S0 = without giving, S1 = 2.5 kg / plot and            S2 = 5 kg / plot. Organic Liquid Fertilizer Factor Super ACI (A) divided into 3 levels ie A1 = 1 cc / l, A2 = 2 cc / l, A3 = 3 cc / l. The parameters measured were plant height (cm), number of branches (branches), leaf number (strands), number of fruits per plant (fruit), fruit weight per plant (g), and fruit length (cm), number of fruit per plot (fruit). Results showed that administration of solid waste (sludge) has significant effect on the parameters of plant height, number of branches, number of leaves, number of fruit per plot, number of fruits per plant, fruit weight per plant, and length of fruits per plant. With a dose of the best applications that S2 (5 kg / plot). Liquid organic fertilizer Super ACI significant effect on the parameters of the number of fruit per plot, number of fruits per plant, fruit weight per plant and fruit length per plant. Best application that A3 (3 cc / l). combination of solid waste (sludge) with a liquid organic fertilizer Super ACI provides the interaction parameter the number of fruit per plot, number of fruits per plant, fruit weight per plant, and length of fruits per plant. With the combination of the best application doses solid waste (sludge) 5 kg / plot with a liquid organic fertilizer concentrations Super ACI       3 cc / l. Key words:eggplant, Sludge and liquid organic fertilize